HUBUNGAN KELINCAHAN DENGAN KETERAAMPILAN MENGGIRING BOLA PADA TEAM SEPAKBOLA SMA NEGERI 1 KAMPAR - Suhairi Anwar; Ramadi '; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The problem in this research is to investigate the relationship Agility With Ball Dribbling Skills In Football Team Sma Negri 1 Kampar.Populasi in this study is Sma Negri Soccer Team 1 Kampar amounting to 24 people using total sampling technique in which all the population sampled, to obtain Dogging research data used test Run and dribbling skills test. Data were analyzed by simple and multiple product moment. Testing normality of variables X, L0maks < Ltable or 0.1217 <0.173, and testing normality variable Y, L0maks < Ltable or 0.1678 <0.173 summed up everything normal distribution, then performed a correlation analysis that rcount is greater than the rtabel, where rcount = = 0.002 < rtable = 0,404. Thus, it means there is no significant relationship between agility to dribble. Thus it is clear that to get good results lead not only necessary agility course, but still bnyak factors other conditions. One of them is flexibility. From the analysis it is also clear that if connect with agility, there is no relationship, then it is suggested to look at other physical conditions such as spasticity in Negri Sma Soccer Team 1 KamparKeywords: Agility, Dribbling Skills